2016
DOI: 10.1111/gcb.13431
|View full text |Cite
|
Sign up to set email alerts
|

Grazing intensity significantly affects belowground carbon and nitrogen cycling in grassland ecosystems: a meta‐analysis

Abstract: Livestock grazing activities potentially alter ecosystem carbon (C) and nitrogen (N) cycles in grassland ecosystems. Despite the fact that numerous individual studies and a few meta-analyses had been conducted, how grazing, especially its intensity, affects belowground C and N cycling in grasslands remains unclear. In this study, we performed a comprehensive meta-analysis of 115 published studies to examine the responses of 19 variables associated with belowground C and N cycling to livestock grazing in global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
284
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(334 citation statements)
references
References 78 publications
(148 reference statements)
18
284
3
1
Order By: Relevance
“…Our meta‐analysis also found that drought significantly increased R/S (Figure c; Table S1), which was consistent with the results from Pallardy and Rhoads () and Aspelmeier and Leuschner (). Increased R/S is a plant avoidance mechanism in response to drought when drought increases the proportion of RB relative to aboveground biomass (Hermans, Hammond, White, & Verbruggen, ; Hodge, ; Zhou et al, ). Meanwhile, the response of R/S to drought varied among plant functional types (Figure ), which might be attributed to the different strategies of plant functional types to obtain water and nutrients and distribution of RB at different soil profile (Daryanto et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our meta‐analysis also found that drought significantly increased R/S (Figure c; Table S1), which was consistent with the results from Pallardy and Rhoads () and Aspelmeier and Leuschner (). Increased R/S is a plant avoidance mechanism in response to drought when drought increases the proportion of RB relative to aboveground biomass (Hermans, Hammond, White, & Verbruggen, ; Hodge, ; Zhou et al, ). Meanwhile, the response of R/S to drought varied among plant functional types (Figure ), which might be attributed to the different strategies of plant functional types to obtain water and nutrients and distribution of RB at different soil profile (Daryanto et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Well‐designed experiments are thus necessary to comprehensively examine the response of diverse root traits and other ecosystem processes to drought (Fotelli et al, ). Third, global climate change often incorporates simultaneous changes in multiple environmental factors (e.g., rising temperature, precipitation, nitrogen addition, and elevated CO 2 ), which may interactively influence root traits (Zhou et al, ). However, despite the fact that our current study indicated the importance of drought on root traits, the interactions between drought and multiple climate factors on root traits in terrestrial ecosystems still remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 115 published studies found that grazing intensity affected the magnitude and direction of most belowground C and N pools and fluxes, with light grazing contributing to soil C and N sequestration, whereas moderate and heavy grazing significantly increasing C and N losses (Zhou et al, 2017). A global review and meta-analysis of 83 studies of extensively managed grasslands found an interaction of grazing intensity and regional climate for soil C accumulation (Abdalla et al, 2018).…”
Section: Presence Of Legumesmentioning
confidence: 99%
“…Livestock grazing is a global land‐use activity with a wide‐range of effects on key biotic and abiotic variables and hence on terrestrial carbon cycling (Selsted et al., ; Zhou et al., ). Because most previous grazing experiments have lasted <10 years (Zhao et al., ; Zhou et al., ), they were unable to detect the underlying mechanisms of how long‐term grazing affects soil carbon processes by changing biotic and abiotic parameters. Although the individual effects of nitrogen deposition and precipitation change on soil respiration are relatively well understood, how their effects on soil respiration are altered by long‐term grazing have rarely been assessed, especially under different grazing intensities.…”
Section: Introductionmentioning
confidence: 99%